Optimal Timing of VT Ablation for Patients with ICD Therapies - Radinovic, Andrea; Baratto, Francesca; Della Bella, Paolo (Current cardiology reports, 2020)
Purpose of Review Optimal timing for catheter ablation of ventricular tachycardia is an important yet unresolved subject. While it is clear that it is indicated with relatively advanced disease, it is still uncertain how early it should be recommended. In this review, we will focus on the status of timing of catheter ablation for VT in patients with ICD therapies. Recent Findings The latest expert consensus statement added a new timing indication for catheter ablation after the first episode of monomorphic VT, in patients with ischemic heart disease and an ICD. Summary Early referral for catheter ablation reduces the number of VT recurrences; however, an impact on mortality has not been demonstrated yet. Guidelines and real-world data alike show an increasing trend to refer patients after the first VT episode in ICD patients. Randomized clinical trials powered to assess mortality are essential in order confirm the beneficial effects of an early strategy.